Effect of ω-3 fatty acid supplementation on endothelial function, endogenous fibrinolysis and platelet activation in male cigarette smokers. Issue 3 (26th November 2012) - Din, Jehangir N; Archer, Rachel M; Harding, Scott A; Sarma, Jaydeep; Lyall, Karin; Flapan, Andrew D; Newby, David E
Abstract : Objective: The effects of ω-3 fatty acids on endothelial function, fibrinolysis and platelet function are uncertain. We investigated the effects of ω-3 fatty acid supplementation on endothelial vasomotor function, endogenous fibrinolysis, and platelet and monocyte activation in healthy cigarette smokers; a group at increased risk of myocardial infarction. Design, setting, participants: Twenty cigarette smokers were recruited into a randomised, double-blind, placebo-controlled, crossover trial of ω-3 fatty acid supplementation. Intervention: ω-3 fatty acid supplements (2 g/day) or placebo for a 6-week period. Main outcome measures: Peripheral blood was taken for analysis of platelet and monocyte activation, and forearm blood flow (FBF) was assessed in a subset of 12 smokers during intrabrachial infusions of acetylcholine, substance P and sodium nitroprusside. Stimulated plasma tissue plasminogen activator (t-PA) concentrations were measured during substance P infusion. Results: All vasodilators caused dose-dependent increases in FBF (p<0.0001). Compared with placebo, ω-3 fatty acid supplementation led to greater endothelium-dependent vasodilatation with acetylcholine and substance P (p=0.0032 and p=0.056). Substance P caused a dose-dependent increase in plasma t-PA concentrations (p<0.0001) that was greater after ω-3 fatty acid supplementation compared with placebo (8.8±2.3 IU ml −1 vs 3.6±1.1 IU ml −1 ; p=0.029). ω-3 fatty acids did not affect platelet-monocyte aggregation, platelet P-selectin or CD40L, or monocyte CD40. Conclusions: We have demonstrated for the first time that ω-3 fatty acids augment acute endothelial t-PA release and improve endothelial vasomotor function in cigarette smokers. Improved endogenous fibrinolysis and endothelial function may represent important mechanisms through which ω-3 fatty acids confer potential cardiovascular benefits.